2008
DOI: 10.1108/09544780810842901
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic approach to conducting a successful benchmarking expedition

Abstract: PurposeThe purpose of this paper is to provide a conceptual framework for conducting a benchmarking visit/expedition.Design/methodology/approachRecent articles on the models of benchmarking are reviewed and used to construct a seven‐step benchmarking visit/expedition framework that is subsequently tested by applying it to facilitate a benchmarking expedition for Dubai Holding Group (DHG) with United Utilities, Bradford and Bingley and the Marriot Hotel, all of the UK.FindingsThe paper finds that good planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Hence, this model could be improved and evolving best practice can be incorporated within this model (Anand and Kodali, 2008). Other models for implementing benchmarking which could be used are that of the European Foundation for Quality Management (EFQM), that of Bhutta and Huq (1999), Zairi and Baidoun (2003), Marwa and Zairi (2008) and others, but they are too process-oriented and costly to implement. Furthermore, the amount of effort and investment required for participating is consequential.…”
Section: Jfm 132mentioning
confidence: 99%
“…Hence, this model could be improved and evolving best practice can be incorporated within this model (Anand and Kodali, 2008). Other models for implementing benchmarking which could be used are that of the European Foundation for Quality Management (EFQM), that of Bhutta and Huq (1999), Zairi and Baidoun (2003), Marwa and Zairi (2008) and others, but they are too process-oriented and costly to implement. Furthermore, the amount of effort and investment required for participating is consequential.…”
Section: Jfm 132mentioning
confidence: 99%
“…Hence, this model could be improved, and evolving best practice can be incorporated within this model (Anand and Kodali, 2008). Other models for implementing benchmarking which could be used are that of the EFQM, that of Bhutta and Huq (1999), Zairi and Baidoun (2003), Marwa and Zairi (2008) and others, but they are too process oriented, costly to implement. Furthermore, the amount of effort and investment required for participating is consequential.…”
Section: Studies On Benchmarking Benefits Globallymentioning
confidence: 99%
“…Found that participation in quality award process strengthened their quality improvement process and gained quality awards. Benchmarking practices is one of the TQM techniques, practiced in a case study (Simmy and Zairi, 2008) suggested that benchmarking visits are a cost to business and should therefore be designed and executed with outmost care to achieve desired outcomes. Kiran et al, (1995), through their theoretical studies said that joint implementation of JIT and TQM in the industries are outperforming in improving the quality of products and processes as well as customer satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%